Study on the satisfaction of young employees in Chinese banks - Zhu, Xuan (2022)
The purpose of this paper is to study the influencing factors of job satisfaction of young employees in China's banking industry. At present, the rapid development of China's banking industry and the increasingly fierce competition in the industry, coupled with the fact that young employees have different values and characteristics from their predecessors, have led to the high turnover rate of young employees in China's banking industry. Through the questionnaire of more than 200 young employees in China's banking industry, this paper studies whether the factors of work itself, training, career development, working environment, colleague relationship, superior support, pay and benefit, policy and management, and demographics affect job satisfaction. The final results show that for young employees of China's banks, the job itself, colleague relations, career development, pay and benefit have a positive impact on job satisfaction, while the working environment, superior support, policy and management, and training have no significant impact on job satisfaction. For demographic factors, age, job tenure, marital status and job position have an impact on job satisfaction, while gender and educational background have no significant impact on job satisfaction.